Pope John Paul II’s Encounters with Polish Jews - Krajewski, Stanislaw (Studies in Christian-Jewish Relations, 2020)
This article examines the official encounters in Poland of Pope John Paul II with representatives of the Polish Jewish community. This study includes a first-hand account of the atmosphere of the meetings and their backgrounds. This article also offers an analysis of the Pope’s addresses.